2020
DOI: 10.1007/s40194-020-00959-3
|View full text |Cite
|
Sign up to set email alerts
|

Arc-welding based additive manufacturing for body reinforcement in automotive engineering

Abstract: Arc-welding based additive manufacturing is a cost-efficient, productive technology which has been shown to be capable of producing high-integrity components. It is suggested that in automotive engineering, this manufacturing process can be used to reinforce body components by generating stiffening elements. Benefits of this method could be more flexural rigidity with comparatively lower material volume. In the current study, wire arc additive manufacturing (WAAM) with an advanced short arc welding process wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…AM strengthening has been developed by considering use of wire-and-arc additive manufactured (WAAM) stiffener (Figure 1) on one side of the plate. Similar solutions were explored for stiffening of I-beam web [5] or body reinforcement of automotive engineering [6]. In this paper, different arrangements of WAAM plate stiffeners and comparison to traditional prismatic stiffener are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…AM strengthening has been developed by considering use of wire-and-arc additive manufactured (WAAM) stiffener (Figure 1) on one side of the plate. Similar solutions were explored for stiffening of I-beam web [5] or body reinforcement of automotive engineering [6]. In this paper, different arrangements of WAAM plate stiffeners and comparison to traditional prismatic stiffener are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional stiffening structures produced by WAAM can adapt sheets or profiles specifically to certain applications. Josten and Höfemann [5] demonstrated that single-layer grids on flat car body sheets could increase the bending stiffness by 50-90%.…”
Section: Introductionmentioning
confidence: 99%
“…In the industry, this example from everyday life is often met when welding [1-3], screwing, or joining two flexible parts: if the operations of fixation are not executed in a well designed order, these parts may not be well assembled considering the project requirements. Additive manufacturing of stiffeners on metal sheets produces the same kind of issues [4,5]. It generates some deflections on these parts.…”
Section: Introductionmentioning
confidence: 99%